Augmenting the Left. Issue 2 (3rd April 2018) - Kingsmith, A. T.; von Bargen, Julian; Murray, Karen Bridget; Latham, Robert
ABSTRACT: Nine papers with respective replies, grounded in Marxist traditions, analyse the potential for social transformation through a reinvigorated radical Left, all within the context of the ascendance of the far Right worldwide. Papers variously take up new lines of analysis, while also identifying and theorizing strategies and possibilities for increasing and deepening popular participation and support on the far Left. Authors are drawn variously from Australia, Britain, Canada, Cyprus, France, Greece, Ireland, Japan, Slovenia, and the United States. They comprise new scholars as well as established and leading theorists and activists. Collectively, the papers address three predominant themes: the changing and expanding conceptualization on the Left of contemporary capitalism; what it means to speak of 'the people' in relation to political action today; and approaches to mobilizing and organizing that people. The wide-ranging but focused and rigorous insights produced across the pieces are aimed at speaking to scholars, students, observers, and activists who seek knowledge about the challenges and opportunities the Left faces today.